Programming Languages and Systems 6th Asian Symposium, APLAS 2008, Bangalore, India, December 9-11, 2008, Proceedings - Ramalingam, G.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
This book constitutes the refereed proceedings of the 6th Asian Symposium on Programming Languages and Systems, APLAS 2008, held in Bangalore, India, in December 2008. The 20 revised full papers presented together with 3 invited talks were carefully reviewed and selected from 41 submissions. The symposium is devoted to all topics ranging from foundational to practical issues in programming languages and systems. The papers cover topics such as semantics, logics, foundational theory, type systems, language design, program analysis, optimization, transformation, software security, safety, verification, compiler systems, interpreters, abstract machines, domain-specific languages and systems, as well as programming tools and environments.
Abductive Inference for Reasoning about Heaps -- A Sound Floating-Point Polyhedra Abstract Domain -- A Flow-Sensitive Region Inference for CLI -- Context-Sensitive Relevancy Analysis for Efficient Symbolic Execution -- Static Detection of Place Locality and Elimination of Runtime Checks -- Certified Reasoning in Memory Hierarchies -- The Complexity of Coverage -- Game Characterizations of Process Equivalences -- Extensional Universal Types for Call-by-Value -- Harnessing the Multicores: Nested Data Parallelism in Haskell -- Minimal Ownership for Active Objects -- Type-Based Deadlock-Freedom Verification for Non-Block-Structured Lock Primitives and Mutable References -- Reasoning about Java’s Reentrant Locks -- ML Modules and Haskell Type Classes: A Constructive Comparison -- The Essence of Form Abstraction -- On Affine Usages in Signal-Based Communication -- Abstraction of Clocks in Synchronous Data-Flow Systems -- From Authorization Logics to Types for Authorization -- Interface Types for Haskell -- Exception Handlers as Extensible Cases -- Sound and Complete Type Inference for a Systems Programming Language -- An Operational Semantics for JavaScript -- JavaScript Instrumentation in Practice.
Keywords: Programming languages (Electronic computers).; Software engineering; Operating systems (Computers).; Computer logic; Computer programming; Programming Languages, Compilers, Interpreters; Software Engineering/Programming and Operating Systems; Operating Systems; Software Engineering; Logics and Meanings of Programs; Programming Techniques